Analisis Perilaku Herding pada Indeks Sri-Kehati saat Kondisi Pandemi COVID-19 - Simanjuntak, Elvira Maytasya; Dewi, Vera Intanie (E-Jurnal Akuntansi; Vol 32 No 3 (2022)DO - 10.24843/EJA.2022.v32.i03.p16, 2022)
This study aims to analyze the presence of herding behavior on the SRI-KEHATI Index for the period January 2, 2020 to December 30, 2021. Herding behavior can be identified through the relationship between stock return dispersion and market return. In calculating stock return dispersion using the Cross Sectional Absolute Deviation or CSAD method. This study uses data on the daily closing price of the SRI-KEHATI index and data on the daily prices of 17 company stocks that are always on the SRI-KEHATI index during the observation period. The analytical method used is ordinary least square regression analysis. The time period used is when the market is in a state of uncertainty which is indicated by more herding behavior. The results showed that there was no indication of herding behavior on the SRI-KEHATI Index during the COVID-19 Pandemic condition which was marked by no non-linear relationship between the CSAD variable and the squared market return variable. Keywords: Herding Behavior; CSAD; Market Return.